2013
DOI: 10.26784/issn.1886-1881.v10i19.270
|View full text |Cite
|
Sign up to set email alerts
|

Arte figurativa e arte contabile. Le tavolette della biccherna del comune di Siena (XIII-XVII secolo)

Abstract: Fra le arti figurative comprese in quelle cosiddette “belle”, cioè le forme di attività che, secondo l'opinione del Vasari, hanno esclusivamente un fine di bellezza, un valore estetico, come l'architettura, la danza, la poesia, la pittura, la scultura e la musica, in questo articolo focalizziamo l'attenzione sulla pittura e su di una sua particolare espressione e manifestazione, irripetibile ed originalissima.Le composizioni pittoriche che rappresentano eventi e situazioni di vita vissuta o configurazioni di a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We add to rare studies that have shown the importance of art in organizing (e.g. Barnes and Newton, 2017) and earlier references to the Biccherna panels (Catturi, 2013; Yamey, 1989), by showing that artworks can contribute to governance.…”
Section: Governance and Visual Settingsmentioning
confidence: 81%
See 2 more Smart Citations
“…We add to rare studies that have shown the importance of art in organizing (e.g. Barnes and Newton, 2017) and earlier references to the Biccherna panels (Catturi, 2013; Yamey, 1989), by showing that artworks can contribute to governance.…”
Section: Governance and Visual Settingsmentioning
confidence: 81%
“…We add to rare studies that have shown the importance of art in organizing (e.g. Barnes and Newton, 2017) and earlier references to the Biccherna panels (Catturi, 2013;Yamey, 1989), by showing that artworks can contribute to governance. Meyer et al (2018) further identify four 'affordances' of the visual pertinent to our study of the Biccherna panels.…”
Section: The Visualmentioning
confidence: 82%
See 1 more Smart Citation